Interesterification of engkabang (Shorea macrophylla) fat - canola oil blend with lipase from Candida antarctica to simulate the properties of lard - Mohamed Roslan, Nur Illiyin; Marikkar, Jalaldeen Mohamed Nazrim; Loke, Mei Key; Musthafa, Shuhaimi; Basri, Mahiran; Mat Saari, Miskandar (Japan Oil Chemists' Society, 2014)
A study was carried out to compare the composition and thermal properties of lard (LD) and engkabang fat (EF) - canola oil (CaO) blend interesterified with Candida antartica lipase (C. antartica). A fat blend EF-4 (40% EF in CaO) was prepared and interesterified using C. antartica lipase at 60°C for different time intervals (6 h, 12 h and 24 h) with 200 rpm agitation. The fat blends before and after interesterification were compared to LD with respect to their slip melting points (SMP), fatty acid and triacyglycerol (TAG) compositions, melting, solidification and polymorphic properties. Result showed that the slip melting point (SMP) of the fat blend interesterified for 6 h was the closest to that of LD. The solid fat content (SFC) values of fat blends interesterified for 12 and 24 h were found to become equal to those of LD within the temperature range of 0 to 20°C. In addition, all three interesterified blends had SFC values similar to those of LD within the temperature range of 30-40°C. According to thermal analysis, the transition of the fat blend interesterified for 24 h appearing at -2.39°C was similar to the low melting thermal transition of LD and the transition of the fat blend interesterified for 12 h appearing at 26.25°C was similar to the high melting thermal transition of LD. However, there is no compatibility between LD and all three interesterified blends with regard to polymorphic behaviour.